NLRP3 Inflammasome Activation in Cancer: A Double-Edged Sword - Hamarsheh, Shaima'a; Zeiser, Robert (Frontiers in Immunology, 2020)
Inflammation is involved in tumor development and progression as well as antitumor response to therapy. In the past decade, the crosstalk between inflammation, immunity and cancer have been investigated extensively, which led to the identification of several underlying mechanisms and cells involved. The formation of inflammasome complexes leads to the activation of caspase-1, production of interleukin (IL)-1β and IL-18 and pyroptosis. Multiple studies have shown the involvement of NLRP3 inflammasome in tumorigenesis. Conversely, other reports have indicated a protective role in certain cancers. In this review, we summarize theses contradictory roles of NLRP3 inflammasome in cancer, shed the light on oncogenic signaling leading to NLRP3 activation and IL-1β production and outline the current knowledge on therapeutic approaches.